Social and Emotional Learning Benefits of Pollinator Gardens - Bateman, Anna. (Tufts University. Tisch Library., 2023)
Thesis (M.A.)--Tufts University, 2023.; Submitted to the Dept. of Education.; Advisors: Kathryn Davies, and David Hammer.; Committee: Julia Gouvea.; Keyword: Environmental education.